Analisis Yuridis Kasus Pelecehan Seksual Yang Dilakukan oleh Anggota Tentara Nasional Indonesia - Karina Hasiyanni Manurung; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Sexual harassment is a serious problem that is rampant throughout Indonesia, where it affects various levels of society. The existence of sexual harassment perpetrators in the military is a complicated focal point because it contradicts the main task of the military which should uphold the values of security and state integrity. This research will discuss the criminal liability of members of the Indonesian National Army (TNI) who commit sexual harassment and how law enforcement against members of the Indonesian National Army (TNI) who commit sexual harassment. This research uses normative juridical method with statutory approach and conceptual approach. Through strict law enforcement, it is hoped that a system can be created that can prevent and eradicate acts of sexual harassment among the military, so that the integrity and public confidence in the state defense institutions are maintained.